Analisa Produktivitas Tiang Menggunakan Alat Pancang Diesel Hammer Pada Proyek Pembangunan Gedung Kantor Pengadilan Agama Dataran Hunipopu - Ramona Istiqamah Marasabessy; Henriette Dorothy Titaley; Maslan Abdin (Indonesian Society of Applied Science, 2026)
The pile driving process is a crucial stage in foundation construction, ensuring the stability and strength of the building structure. Piling can be done with various types of tools, one of which is a diesel hammer. Diesel hammers are renowned for delivering significant impact energy to piles, enabling effective and efficient soil penetration. The purpose of this research is to determine the cycle time of the piling process and to determine the productivity of piling using diesel hammer tools. The method used in this research is direct observation in the field. The results obtained from the research were the average cycle time in the piling process using a diesel hammer piling tool at 101 points for 16 days, which was 50.35 minutes during normal working hours and 59.94 minutes during overtime. The productivity of the diesel hammer on the work of the Religious Court Office Building was the lowest on the first day, with a productivity value of 10.48 m/hour, and the highest occurred on day fifteen, with a productivity value of 17.25 m/hour. During overtime working hours, the highest productivity was recorded on the fifteenth day at 16.71 m/hour, while the lowest was on the first day at 4.01 m/hour.